Presence of serum autoantibodies to vacuolar H+‐ATPase in patients with renal tubular acidosis. (1st March 2019) - Xu, Chao; Li, Yanping; Ying, Hui; Pan, Yan; Shi, Ranran; Lin, Xiaoyan; Gao, Ling
Abstract: Objective: Concomitant presence of renal tubular acidosis (RTA) and autoimmune diseases is indicative of the potential role of immune factors in the pathogenesis of RTA. Our study aimed to detect the serum antibodies to renal tubular epithelial cells in RTA patients. Methods: We enrolled 11 RTA patients, eight primary Sjögren's syndrome (pSS) patients and eight healthy controls (HC). Serum biochemical test, urinary regular test, and 24 hours urinary protein quantification were measured using a fully automated analyzer. Immunofluorescence assay was performed to detect the antibodies to subunit B1 and subunit B2 of v‐H+‐ATPases (adenosine triphosphatases) in the serum of the participants. Results: Clinically, RTA patients showed hyperchloremia, acidosis and paradoxical alkaline urine. We detected the serum antibodies to renal tubular epithelial cells and there were 6/11 positive in RTA patients, much higher than that in the pSS group (0/8) and the HC group (0/8). Subsequently, we demonstrated that in normal renal tissue, the B1 subunit of v‐H+‐ATPase specifically expressed in intercalated cells, while the B2 subunit continuously expressed along the lumen of renal tubular epithelial cells. Moreover, the antibody to subunit B1/B2 of v‐H+‐ATPase was positive in the sera of 6 RTA patients (54%), while it was negative in both the pSS and HC group. Conclusions: We detected the presence of serum autoantibodies to subunit B1 and subunit B2 of v‐H + ‐ATPase in RTA patients. Our findings may provide novel mechanism insights into the pathogenesis of RTA and the potential diagnostic utility of antibodies to v‐H + ‐ATPase in the classification of RTA.